2016
DOI: 10.5314/wjd.v5.i2.109
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric ocular rosacea, a misdiagnosed disease with high morbidity: Proposed diagnostic criteria

Abstract: Ocular rosacea is an important and underdiagnosed chronic inflammatory disorder observed in children. A clinical spectrum ranging from chronic eyelid inflammation, recurrent ocular redness, photophobia and/or hordeola/chalazions and conjunctival/corneal phlyctenules evolving to neovascularization and scarring may occur. Visual impairment and consequent amblyopia are frequent and corneal perforation although rare is the most feared complication. Ocular manifestations usually precede cutaneous lesions. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Cetinkaya et al 45 have described pediatric ocular rosacea as a combination of meibomian gland disease, chronic blepharitis, recurrent chalazia along with long standing symptoms of ocular irritation, redness and photophobia which do not respond to routine medical treatment. A recent publication by Coimbra et al 46 have given a proposed diagnostic criterion according to which if ≥3 of the five criteria are present ( Table 3).…”
Section: Diagnosis Of Pediatric Ocular Rosaceamentioning
confidence: 99%
“…Cetinkaya et al 45 have described pediatric ocular rosacea as a combination of meibomian gland disease, chronic blepharitis, recurrent chalazia along with long standing symptoms of ocular irritation, redness and photophobia which do not respond to routine medical treatment. A recent publication by Coimbra et al 46 have given a proposed diagnostic criterion according to which if ≥3 of the five criteria are present ( Table 3).…”
Section: Diagnosis Of Pediatric Ocular Rosaceamentioning
confidence: 99%
“…5 In addition, ocular involvement tends to be more common in pediatric patients, with eye manifestations more commonly preceding cutaneous features. 6 While treatment guidelines for rosacea are available, these are based on evidence that does not include children. 7,8 Due to the lack of consensus on the standard of care for rosacea specific to the pediatric population, we performed a systematic review of published literature aimed at identifying the efficacy of reported treatments used for pediatric rosacea to support future guideline development.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the subtypes mentioned above, there is also a pediatric specific subtype of rosacea referred to as aseptic facial granuloma (AFG) 5 . In addition, ocular involvement tends to be more common in pediatric patients, with eye manifestations more commonly preceding cutaneous features 6 …”
Section: Introductionmentioning
confidence: 99%
“…occurs in 40% of people of a medical profession such as doctors, nurses, and physiotherapists, and in 33.7% of medical students and 23.5% of drug abusers. Ocular demodicosis can be a result of the presence of mites on the facial skin [17][18]. Demodex spp.…”
Section: Epidemiologymentioning
confidence: 99%